2015
DOI: 10.1371/journal.pone.0145813
|View full text |Cite
|
Sign up to set email alerts
|

Substrate Stiffness Regulates Proinflammatory Mediator Production through TLR4 Activity in Macrophages

Abstract: Clinical data show that disease adversely affects tissue elasticity or stiffness. While macrophage activity plays a critical role in driving disease pathology, there are limited data available on the effects of tissue stiffness on macrophage activity. In this study, the effects of substrate stiffness on inflammatory mediator production by macrophages were investigated. Bone marrow–derived macrophages were grown on polyacrylamide gels that mimicked the stiffness of a variety of soft biological tissues. Overall,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

8
121
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 133 publications
(136 citation statements)
references
References 44 publications
8
121
0
Order By: Relevance
“…Macrophages cultured on stiffer substrate exhibited increased spreading area and enhanced adhesion, accompanied with elevated classical activation than that of macrophages cultured on softer substrate (Blakney et al, 2012). Macrophage grown on soft substrates produced less proinflammatory cytokines with decreased TLR4 activity than that of the macrophages grown on rigid substrates (Previtera and Sengupta, 2015). The modulation of macrophage function by substrate rigidity is dependent on actin polymerization and RhoGTPase activation (Patel et al, 2012).…”
Section: Discussionmentioning
confidence: 99%
“…Macrophages cultured on stiffer substrate exhibited increased spreading area and enhanced adhesion, accompanied with elevated classical activation than that of macrophages cultured on softer substrate (Blakney et al, 2012). Macrophage grown on soft substrates produced less proinflammatory cytokines with decreased TLR4 activity than that of the macrophages grown on rigid substrates (Previtera and Sengupta, 2015). The modulation of macrophage function by substrate rigidity is dependent on actin polymerization and RhoGTPase activation (Patel et al, 2012).…”
Section: Discussionmentioning
confidence: 99%
“…Much of our knowledge in this area has stemmed from studies performed in the context of biomaterials engineering, since implanted materials clearly alter the biophysical environment, and are known to interact with abundant macrophages . Several groups have found that stiffer materials enhance inflammatory activation, and grooved or fibrous materials promote alternative activation . In some cases, these findings have been correlated with in vivo studies, where materials are implanted within animals and macrophages in the surrounding tissue are characterized .…”
Section: Discussionmentioning
confidence: 99%
“…A and B). With respect to phenotype polarization, several groups have found that culture of macrophages (THP‐1, RAW 264.7, or BMDM) on stiffer materials potentiates inflammatory activation, although there are some reported discrepancies . Nonetheless, subcutaneous implantation of polyethylene glycol hydrogels with different stiffnesses led to greater macrophage recruitment and fibrous capsule thickness in response to stiffer compared to softer materials, suggesting an important ramification of material stiffness on the immune‐mediated foreign body response in vivo .…”
Section: Regulation Of Macrophages By Biophysical Cuesmentioning
confidence: 99%
See 2 more Smart Citations